Religion and Power as Strategic and Tactical Mechanisms of Social Normalization - A. I. Kugay; T. G. Cherkasova (Управленческое консультирование, 2018)
It has long been noted that we are formed by power, penetrating into all spheres of life. However, looking at the rings of history, you notice that political and legal institutions were not built in a spontaneous and abstract way, their design was predetermined by religious maxims rooted in social fabric. Accordingly, power is only a tactical mechanism of social life, as a system of higher spiritual and moral imperatives, meanings and meanings that prescribe a certain behavior to a person, thereby exerting a managerial influence on him. Obviously, the existence and development of Russia in the foreseeable future will be linked to the search for the ruling and intellectual elite of such forms of normalization in the political, legal, social and cultural spheres of life that would not only not contradict social justice — the basic ideal of traditional religious faiths — Orthodoxy, Islam, Judaism, Buddhism, governance, embodied in the evangelical imperative “If any of you wants to become the chief, let him be the whole servant” (St. Mark’s Gospel, 10:43), but also provided, through the separation of powers, the rule of law, political competition, its achievement.